DUKUNGAN KELUARGA DALAM PENCEGAHAN PENULARAN ULANG (REINFEKSI) PADA PENYINTAS COVID 19 DENGAN DIABETES MELLITUS (DM) - Raudhotun Nisak (Jurnal Keperawatan dan Kesehatan Masyarakat Cendekia Utama, 2022)
Background: Covid-19 is a type of disease that can be transmitted easily to other people. People who have experienced Covid-19 infection (Covid-19 survivors) will have immunity against this disease. However, several studies have shown that survivors of Covid-19 can be infected a second time (reinfection). Covid-19 survivors with DM need to get family support regarding the prevention of reinfection considering that DM patients with uncontrolled sugar levels have T cell dysfunction which can cause impaired B cell activation and reduced antibody production. Objective: This study aims to analyze family support in preventing reinfection in Covid-19 survivors with DM. Methods: This study uses a qualitative method with a phenomenological approach. The time of this research began in December 2020-January 2021 with a sample of 6 participants in Pitu District, Ngawi Regency. The research instrument used was a voice recorder/mobile phone, field notes/field notes and interview guidelines. Results: This study resulted in 4 themes, informational support (sub-themes: information, advice, advice, emotional support (sub-themes: enthusiasm, empathy, concern), instrumental support (sub-themes: energy, food, sources of funds), appraisal support/award (sub-themes: strengthening, recognition, appreciation) Conclusion: family support is very much needed and important for Covid-19 survivors with DM in an effort to prevent Covid-19 reinfection.